Report on the 4th International Martial Arts and Combat Sports Scientific Society (IMACSSS) Symposium (Revista de Artes Marciales Asiáticas, 2016)
The report deals with the symposium of the International Martial Arts and Combat Sports Scientific Society (IMACSSS) which was held as a part of the 10th International Conference on Kinanthropology at Masaryk University. The symposium was organised by the Department of Gymnastics and Combatives of Faculty of Sports Studies, Masaryk University, Brno, the Czech Republic. The symposium was attended by 20 members who contributed their knowledge and experience, which provoked the international cooperation aimed at spreading and developing experience with training in martial arts and combat sports. The members of the symposium discussed new approaches and knowledge in martial arts, combat sports, self-defence and education in security field. Presented topics showed the progress and continuous development in the field of martial arts and combat sports at the scientific level.